2022
DOI: 10.1016/j.sjbs.2021.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of salinity stress effects on agro-physiological traits of wheat by auxin, glycine betaine, and soil additives

Abstract: Soil salinity is a major constraint to wheat production; it causes a severe reduction in wheat growth and yield. Alleviation of salinity effects on physiological, biochemical, and yield of wheat cultivars; Sids 14 and Misr 3 using some soil additions (control, Molasses and Humic acid), compatible solutes, and growth regulators (water as control, Naphthalene acetic acid, and Glycine betaine) were investigated in salt-affected soils. Results indicated that Misr 3 was superior to Sids 14 in all studied characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…In contrast, NAA application significantly inhibited the accumulation of H 2 O 2 and MDA, but increased activity of antioxidant enzymes including SOD, CAT and POD in alkalinity-stressed chufa plants compared with control plants and alkalinity-treated plants alone, suggesting that NAA activated adaptive mechanisms against oxidative damages in stressed plants. These findings demonstrate that NAA-application increased antioxidant activity to protect chufa plants against oxidative damage associated with alkalinity, as evidenced by the observed decrease in MDA concentration, which are in line with previous studies ( Olaiya & Anyanwu, 2013 ; Ullah & Sajjad, 2017 ; Khedr et al., 2022 ; Muhammed et al., 2022 ). We suggest that chufa plant is able to significantly increase the activity of antioxidant enzymes in order to resist alkaline stress.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, NAA application significantly inhibited the accumulation of H 2 O 2 and MDA, but increased activity of antioxidant enzymes including SOD, CAT and POD in alkalinity-stressed chufa plants compared with control plants and alkalinity-treated plants alone, suggesting that NAA activated adaptive mechanisms against oxidative damages in stressed plants. These findings demonstrate that NAA-application increased antioxidant activity to protect chufa plants against oxidative damage associated with alkalinity, as evidenced by the observed decrease in MDA concentration, which are in line with previous studies ( Olaiya & Anyanwu, 2013 ; Ullah & Sajjad, 2017 ; Khedr et al., 2022 ; Muhammed et al., 2022 ). We suggest that chufa plant is able to significantly increase the activity of antioxidant enzymes in order to resist alkaline stress.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the reported findings of Khedr et al (2022), when they showed that the rice cultivar Misr 3 exposed to high salt stress resulted in higher proline content, compared to plants not suffering from salt stress. Proline levels increased when wheat leaves were exposed to water stress, whereas silica application reduces accumulation of proline (Khedr et al, 2022). We argue that the accumulation of proline can be an indicator of drought stress-related damage.…”
Section: Elsupporting
confidence: 93%
“…The majority of the H 2 O 2 produced by the catalysis of SOD remained biologically toxic. Following drought stress, the increased rate of SOD activity was lower in drought-tolerant genotypes than in droughtsensitive genotypes; however, the increased rate of CAT and POD activity and total antioxidant capacity was higher in the drought-tolerant genotypes (Simova-Stoilova et al, 2008;Hussain et al, 2021;El-Ashry et al, 2022;Khedr et al, 2022). Thus, the production of H 2 O 2 due to the activated SOD enzyme can function in oxidative stress signaling and can act as a secondary messenger to protect reactions leading to induced CAT and POD activity in plants (Anjum et al, 2011;Hussain et al, 2021;Abd El-Mageed et al, 2022;El-Ashry et al, 2022).…”
Section: Elmentioning
confidence: 99%
“…Plant membrane stability, chloroplast function and Rubisco activity can be shifted by high temperature (Maestri et al, 2002), gas exchange and the effectiveness of PSII would decrease and the chlorophyll will decompose under heat stress (Morales et al, 2003). While GB can improve crop leaf both chlorophyll content and relative water content through leaf spray (Denaxa et al, 2012;Sofy et al, 2020;Khedr et al, 2022), which is different from the regulation mechanism of potassium. Although GB benefits plant growth more extensively in the vegetative stage, it can increase the source to sink (leaf to fruit or seed) transportation (Osman, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is also suggested that spraying silicate at low dosage (50-100 mg ⋅ dm -3 ) could enlarge the flower diameter and even accelerate flowering for some Asteraceae species (Attia andElhawat, 2021, Kamenidou et al, 2010). Similarly, betaine (GB) as a more commonly used organic biostimulant can increase plant stomatal conductance, CO 2 assimilation rate, leaf chlorophyll and relative water content (Denaxa et al, 2012), while cooling down the leaf temperature, increasing quantum yield of PSII and the yield of crop under stress (Khedr et al, 2022). It also improves the activity of catalase, peroxide degrease, superoxide dismutase and nitrate reductase and reduces the concentration of malondialdehyde (MDA), H 2 O 2 and • O 2 -, increasing crop performance under numerous environmental stresses (Rady et al, 2018;Ahmed et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%